2012
DOI: 10.1111/jdv.12036
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of actinomycetoma foot – our experience with ten patients

Abstract: Ramam regimen was found to be quite effective in treating patients of actinomycetoma with only minimal bony involvement, while Welsh regimen and its modification should be used in case of severe disease due to amikacin being more sensitive than gentamicin in treating resistant organisms. Intensive phase of Modified Welsh regimen can be extended to five cycles in case of extensive bony involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Currently, actinomycetoma is treated with a combination of antimicrobial agents consisting of trimethoprim‐sulfamethoxazole and an aminoglycoside . The aminoglycoside differs by country; in both Mexico and Sudan, amikacin sulphate is used (Welsh regimen ), whereas in India, gentamicin is more common (Ramam regimen ). In general, addition of an aminoglycoside to trimethoprim‐sulfamethoxazole has increased the complete cure rate from 30.8% to 42.0% and decreased the patients' non‐response rate from 10.3% to 3.7% .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, actinomycetoma is treated with a combination of antimicrobial agents consisting of trimethoprim‐sulfamethoxazole and an aminoglycoside . The aminoglycoside differs by country; in both Mexico and Sudan, amikacin sulphate is used (Welsh regimen ), whereas in India, gentamicin is more common (Ramam regimen ). In general, addition of an aminoglycoside to trimethoprim‐sulfamethoxazole has increased the complete cure rate from 30.8% to 42.0% and decreased the patients' non‐response rate from 10.3% to 3.7% .…”
Section: Introductionmentioning
confidence: 99%
“…However, Agarwal and colleagues have recently described their experience of two different regimens of medical treatment for patients with actinomycetoma of the foot, and observed that the Ramam regimen was found to be very effective in treating such patients with only minimal bony involvement, while the Welsh regimen and its modification are suitable for more severe cases, because amikacin is more sensitive than gentamicin in the treatment of resistant organisms. The modified Welsh regimen can also be continued for five cycles when there is more extensive bony involvement [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, Agarwal and colleagues have recently described their experience of two different regimens of medical treatment for patients with actinomycetoma of the foot and observed that the Ramam regimen was found to be very effective in treating such patients with only minimal bony involvement, while the Welsh regimen and its modification are suitable for more severe cases, because amikacin is more sensitive than gentamicin in the treatment of resistant organisms. The modified Welsh regimen can also be continued for five cycles when there is more extensive bony involvement 14 . In our patient, ultrasound was used as the modality of imaging and was successful in obtaining a valid diagnosis without much delay (Figure 1).…”
Section: All Authors Contributed To Conception and Design Manuscriptmentioning
confidence: 99%